Hydroseeding for Post-Mining Land Reclamation in Indonesia: Implications for Soil Restoration and Environmental Health - Ayu Putri Ariska; Muhammad Yusuf; Kurniawan Sigit Wicaksono; Reni Ustiatik; Jianxu Wang (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2026)
Post-mining land degradation in Indonesia causes severe declines in soil quality and ecosystem functions, potentially affecting environmental sustainability and public health. Therefore, environmentally friendly reclamation technologies are needed to accelerate vegetation establishment and restore ecological stability in degraded mining landscapes. Although hydroseeding has been widely applied for post-mining revegetation, comprehensive reviews evaluating its implications for soil restoration and environmental health in tropical ecosystems remain limited. This review aims to evaluate the effectiveness of hydroseeding for post-mining land reclamation in Indonesia and to identify current challenges and future improvement opportunities. A structured narrative review was conducted using relevant national and international scientific literature published between 2015 and 2025. The reviewed studies indicate that hydroseeding improves soil structure, increases organic carbon content, enhances nutrient availability, stimulates microbial activity, and accelerates vegetation establishment. Increased plant cover also contributes to erosion control and reduces heavy metal mobilization within the soil-plant-water system, thereby supporting environmental recovery. However, hydroseeding effectiveness remains inconsistent due to climatic and topographic variability, poor soil fertility, limited technical expertise, and restricted availability of adapted native plant species. This review highlights the importance of integrating hydroseeding with soil amendments, indigenous vegetation, and biological restoration approaches to support sustainable post-mining land management. These findings contribute to environmentally friendly reclamation strategies that improve soil restoration, ecosystem stability, and environmental health in tropical post-mining areas.